INTEGRASI RTRW PERTAHANAN DARAT DENGAN RTRW KOTA BANDUNG DALAM RANGKA KETAHANAN WILAYAH - , WIBISONO POESPITOHADI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study was designed to gain an understanding of the Spatial Plan Integration Defence forces with the Spatial Plan of Bandung in order to Resilience Area. Research purposes, to first, assessing the implementation of the integration of Spatial Planning Defence Forces with the Regional Spatial Planning Bandung, second, assess the obstacles encountered in the integration of Spatial Planning Defence Forces with the Regional Spatial Planning Bandung and third, assessing efforts, to the integration of Spatial Planning Defence Forces with the City Spatial Planning area in order Resilience in the city of Bandung. How to research using qualitative methods, techniques of data analisys is mostly done simultaneously with data collection during research in the field with a grand tour and miniature question, data analysis using domain analysis. The study area is located in the city of Bandung, with the techniques of collecting data through observation, interview and literature study. The study found: Integration of Spatial Planning Defense Forces with Spatial Planning Bandung City is still not running. Constraints found in the cooperation between the Military District Command 0618/BS by the City Government in the preparation of Spatial Plan that we should find a solution to solve the Improved Integration of Spatial Conception Defense Forces with the City Spatial Policy: First, the policy at the conceptual level, adjust scientific theory preparation of the Army Defense Spatial with Spatial Bandung urban design approach and the tactics of defense strtegies, through a strategy of scientific development, land defense with the spatial layout of the city. Second, the policy on the juridical level, set up rules and regulations that can support the integration of preparation of the Army Defense Spatial with Spatial City of Bandung in order Resistance Region, through the empowerment strategy of the system. Third, the policy at the operational level, to implement the result of the scientific theory os spatial classification and support the rules and regulations on spatial activity in an integrated program between the Army of Defense Spatial with Spatial Bandung, through a strategy of strengthening the institutional structure. The efforts made by applying the strategy of increasing integration. First, efforts to introduce Spatial Defense Forces to local government. Second, the transformation of science, between the Army of Defense Spatial with Spatial Bandung. Third, make suggestions manufacturing inputs Draft Government Regulation on Spatial Planning Area Defense Treaty. Fourth, create a MOU (Memorandum Of Understanding) Kodim 0618/BS commander with the Mayor of Bandung. Fifth, the establishment of the Office of the Joint One Roof. Sixth, Improving the Quality of Human Resources. Seventh, the socialization of Defense Spatial Land to the entire community of Bandung.